Implementation of Billboard Tax Policy in Supporting Regional Development and Revenue in Gresik Regency - Fawaz Nurul Widad Farahani; Ika Devy Pramudiana; Dian Ferriswara (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the implementation of the advertising tax policy and its role in supporting Regional Original Income (PAD) in Gresik Regency, and identifies barriers that affect its effectiveness. This research adopted a qualitative descriptive approach with data obtained from field studies involving key government officials and supported by relevant literature and regulatory documents. Data were analyzed using McNabb's (2002) framework, which includes grouping data based on constructs, identifying the basis for interpretation, developing generalizations, testing alternative interpretations, and refining theoretical insights. The results indicate that the implementation of the advertising tax policy in Gresik focuses more on intensification than extensification, as intensification is considered more practical and faces less resistance. The licensing and collection processes for advertising tax are carried out based on the legal framework of Regional Regulation No. 8 of 2023 concerning Regional Taxes and Levies and Regent Regulation No. 79 of 2023, which regulates the rental value of advertising as the basis for taxation. Despite significant revenue potential, significant challenges remain, such as inter-agency coordination issues, inadequate data collection, and technical and non-technical barriers in implementing this policy. Unclear legal sanctions and low public awareness and compliance are also inhibiting factors. Nevertheless, advertising tax revenue has generally reached its target, although certain periods were affected by unfavorable economic conditions. This study concludes that to maximize the contribution of advertising tax to local revenue (PAD), improved inter-agency coordination, strengthened institutional capacity, clarified regulatory sanctions, and enhanced public education and engagement are needed. This is expected to support regional fiscal independence in Gresik Regency.